Dialectal and Spoken Language Units in the Newspaper «Volyn»: Stylistic, Lexical and Grammatical Aspects (Linguostylistic Studies, 2018)
Themass media as a sphere of speech activity represent a certain style of material presentation, the purpose of which is to inform and captivate the addressees. The functioning of dialecticisms in the texts are usually studied in comparision with the stylistic norms of the literary language and considered as stylization aimed at interaction with the reader, approaching to his worldview. Intensive use of territorially specific language elements not only in modern fiction works but also in the language of the regional periodicals and radio broadcasting caused an increase of interest to the scientific studies of functional-stylistic peculiarities of the dialectal words in the language of modern mass media.The purpose of the research is to analyze the stylistic motivation of the use of dialectal elements in the language of the periodicals, to find out the genre specification of the penetration of regional spoken units into the language of periodicals and their stylistic function.The article considers the use of the dialectal elements in the language of regional periodical “Volyn” as a means of emotionally-colored attitude of the authors of publications towards certain objects. The importance is placed on the mechanism of comparison, harping different lexical units of the national language in order to achieve artistic and aesthetic effect in journalism. It is proved that the use of geographically differentiated language elements is determined by the expressive function of language in the media. It has the effect of immediacy, informality, communicative interaction with the reader in his own language. Colloquial lexical items in journalism are a manifestation of updating verbalness in the newspaper discourse. The orientation of the media to the daily/spoken language patterns allows to bring the content of the texts closer to the reader's perception.The analytical and journalistic materials of the newspaper «Volyn» use live linguistic units (nouns, adjectives, verbs, adverbs, rarely –numerals) in order to reproduce the regional linguistic flavour, the linguistic characteristics of the subjects of publications. Territorially differentiated units in journalism are a convincing manifestation of the implementation of verbal stylistic means in the newspaper discourse. Dialect and colloquial tokens help to identify the individual elements of the ethno-cultural picture of the world of the inhabitants of Volyn in the language of the regional printed editions.
Keywords: language norm; journalistic style; dialectisms; emotional evaluation; expressive characteristics